Superconducting and conventional electromagnetic launch system for civil aircraft assisted take-off - Bertola, Luca; Cox, Thomas; Wheeler, Patrick; Garvey, Seamus D. (2016)
This paper compares three possible linear motor topologies for an electromagnetic launch system to assist civil aircraft take-off. Assisted launch of civil aircraft has the potential of reducing the required runway length, reducing noise and emissions near airports and improving overall aircraft efficiency through reducing engine thrust requirements. A comparison is made of practical designs of a linear induction motor, a linear permanent magnet synchronous motor and a superconducting linear synchronous motor to propel the A320-200 aircraft. The machine design requirements are established considering aerodynamic and engine performance and allow the aircraft to safely complete the take-off procedure. Analytical design of conventional synchronous and asynchronous linear motor will be compared with finite element analysis. A superconducting synchronous motor design is also considered, accounting for full system losses including the cryocooler power requirement and the mechanical & design constraints necessary for the cooler and the superconducting coils